The Effect of Different Powers of Er:YAGLaser Treatment on Surface Morphology of an Indirect Composite Resin: SEM Evaluation - Garshasbzadeh, Nazanin Zeinab; Mirzaie, Mansoreh; Yassini, Esmael; Shahabi, Sima; Chiniforush, Nasim (Journal of Lasers in Medical Sciences, 2014)
Introduction: Indirect composites are developed to overcome the shortcomings of direct composites but, the adhesion of resin cements to indirect composites is still difficult. The purpose of this study was to evaluate the surface morphology of indirect resin composite treated by different powers of Er:YAGlaser using Scanning Electron Microscopy (SEM). Methods: indirect resin composite blocks (GC Gradia DA2, Japan) with 15× 10 × 10 mm dimensions were made according to manufacturer’s instructions (n=7). The bonding surface of these blocks were polished, then the samples were divided to seven groups as follow: Erbium-Doped Yttrium Aluminum Garnet (Er:YAG )laser with output power of 2, 3, 4, 5, 6,7 W (frequency of 20 Hz, very short pulse) and no treatment. Then, the surfaces were evaluated by scanning electron microscope. Results: The surface treated by Er:YAG laser showed a porous surface. But the amount and pattern of these irregularities differ in each group which may produce micromechanical retention compared to control group with no treatment. Conclusion: Er:YAG laser can be used as an alternative technique for surface treatment and roughening of indirect resin composites.